Wheat maturity in interaction with leaf rust, cultivar resistance, sowing date and climate - Naseri, Bita; Sasani, Shahryar; Fareghi, Sharareh (International Journal of Sustainable Agricultural Research, 2025)
This investigation explored cultivar resistance, sowing date, leaf rust progress, climate, and yield in interaction with wheat maturity. Early maturing wheat cultivars corresponded with a lower area under the leaf rust progress curve (AULRPC), Gaussian parameters, and maximum disease severity compared to late maturity. An earlier disease occurrence was associated with late maturation. A higher yield was associated with early maturation compared to late maturation. A late occurrence of leaf rust corresponded with early maturation. Early sowing was associated with a 182% shorter maturity period than the optimal date. Maturity ranking for the optimal sowing date was 117% lower than very late sowing. There were significant linkages between wheat maturation and leaf rust progress indicators. The number of days with minimum temperature within 5-25˚C and maximum relative humidity ≥ 60% during autumn-winter-spring months was associated with maturity. The mean six-monthly minimum temperature and resistance index were often linked to disease progress indicators. Yield was linked to disease onset, climate, and maturation. Based on principal component analysis, leaf rust progress indicators contributed to the first principal component (PC). The second PC included contributions from wheat yield, sowing date, maturity, and nine months of climatic indicators. Findings provide information necessary to optimize future breeding and epidemiological studies for sustainable wheat production.